(untitled) (Marketing Journal, 2025)
The growing pressure on agricultural resources, rising energy demand, and intensifying climate impacts have compelled many countries to consider innovative dual-use land technologies. Among these, agrivoltaic systems —allowing simultaneous agricultural prod uction and photovoltaic (PV) electricity generation —emerge as a promising strategic direction. For Uzbekistan, where agriculture remains a core pillar of the economy and solar energy resources are among the richest worldwide, agrivoltaics presents a long -term solution linking green growth, energy independence, and environmental sustainability. This paper examines the economic and environmental efficiency of agrivoltaic systems in Uzbekistan using a conceptual approach, without quantitative modeling. The ana lysis focuses on land -use optimization, farm -level energy security, climate resilience, microclimate benefits, carbon reduction potential, and water -use efficiency. It also identifies institutional, financial, and infrastructural barriers hindering broad i mplementation. The study concludes with policy recommendations for enabling agrivoltaics to support national goals outlined in the "Uzbekistan -2030" Strategy, the transition to a green economy, and the modernization of the agricultural sector.